Rola Instytutu Mikołowskiego w upowszechnianiu przekładów literatury słoweńskiej w Polsce w ostatnich latach - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2016)
The Mikołowski Institute’s Role in Promoting Slovenian Literature in Poland in the last years This article focuses on the dissemination of Slovenian literature in Polish by the Rafał Wojaczek Institute in Mikołów between 2012 and 2015. The author approaches the role of publishers in promoting literatures that are viewed from the Polish perspective as marginal using Pierre Bourdieu’s theory of social fields. She points to the mechanisms and motivations of both the publisher and the translators, addresses issues related to graphic design, and examines the impact of paratextuality. The appreciation of non -mainstream literatures, including translations, stems from Bourdieu’s notion of illusio, a belief shared by the Institute’s staff and the team supporting the publishing process (i.e. translators) in the value of literature, translation and publishing, and their aesthetic and social impacts. The interest of the Mikołowski Institute in propagating fringe literatures, its attempts to transfer symbolic Slovenian capital into Polish and its relative autonomy in the publishing market are well worth noting. Key words: peripheral cultures, dominant cultures, translations in 2014, translation choices, intercultural dialogue